Technology Innovations in Education: Their Effects on Student Motivation and Learning Achievement - Mustamin, Kaso; Hasbullah, Bahmid; Husain, Husriani; Mislia, Mislia; Intiardy, Dermawan (International Journal of Educational Research Excellence (IJERE), 2025)
The following article discusses the impact of technological innovation in education on students' motivation and learning achievement. This quantitative case study employed qualitative research methods to collect data through in-depth interviews, direct observation, and document analysis on a sample of secondary school students.The results indicate that the integration of technology, such as digital-based learning applications, learning management systems (LMS), and interactive tools, fosters increased student motivation through learning experiences that are more engaging and interactive. The study also identified significant challenges in the implementation of technology and provided recommendations to facilitate more effective integration.